Efficacy, safety and tolerability of very low-calorie ketogenic diet in obese women with fibromyalgia: a pilot interventional study - Ciaffi, Jacopo; Lisi, Lucia; Mari, Anna; Mancarella, Luana; Brusi, Veronica; Pignatti, Federica; Ricci, Susanna; Vitali, Giorgia; Stefanelli, Nicola; Assirelli, Elisa; Neri, Simona; Naldi, Susanna; et al. (Frontiers in Nutrition, 2023)
Introduction: Obesity can worsen fibromyalgia (FM) and very low-calorie ketogenic diet (VLCKD) is a potential therapeutic option for diseases that share clinical and pathophysiological features with FM. In this pilot interventional study, we investigated the effects of VLCKD in obese women with FM. Methods: Female patients with FM and a body mass index (BMI) ≥ 30 kg/m2 were eligible for VLCKD. The ketogenic phase (T0 to T8) was followed by progressive reintroduction of carbohydrates (T8 to T20). Changes in BMI, Fibromyalgia Impact Questionnaire (FIQ), Hospital Anxiety and Depression Scale (HADS), EuroQol 5D (EQ-5D) and 36-item Short Form Health Survey (SF-36) were evaluated. A change of 14% in FIQ was considered clinically relevant. The longitudinal association between BMI and patient-reported outcomes (PROs) was assessed using generalized estimating equations. Results: Twenty women were enrolled. Two discontinued the intervention. The mean age of the 18 patients who reached T20 was 51.3 years and mean BMI was 37.2 kg/m2. All patients lost weight during the first period of VLCKD and this achievement was maintained at T20. Mean BMI decreased from 37.2 kg/m2 at T0 to 34.8 kg/m2 at T4, 33.5 kg/m2 at T8 and 32.1 kg/m2 at T20 (p<0.001). A significant reduction of mean FIQ from 61.7 at T0 to 37.0 at T4 and to 38.7 at T8 (p<0.001) was observed and it was maintained at T20 with a mean FIQ of 39.1 (p=0.002). Similar results were obtained for HADS, EQ-5D and SF-36. Analysing each participant, the reduction of FIQ was clinically meaningful in 16 patients (89%) at T4, in 13 (72%) at T8 and in 14 (78%) at T20. No significant association was observed between change in BMI and improvement of the PROs over time. Adverse effects were mild and transient. No major safety concerns emerged. Conclusion: These are the first data on the efficacy of VLCKD in FM. All patients achieved improvement in different domains of the disease, which was maintained also after carbohydrate reintroduction. Our results suggest that ketosis might exert beneficial effects in FM beyond the rapid weight loss. This trial is registered on ClinicalTrials.gov, number NCT05848544.